2022
DOI: 10.1038/s41392-022-00987-z
|View full text |Cite
|
Sign up to set email alerts
|

Broadly neutralizing antibodies against Omicron-included SARS-CoV-2 variants induced by vaccination

Abstract: The SARS-CoV-2 Omicron variant shows substantial resistance to neutralization by infection- and vaccination-induced antibodies, highlighting the demands for research on the continuing discovery of broadly neutralizing antibodies (bnAbs). Here, we developed a panel of bnAbs against Omicron and other variants of concern (VOCs) elicited by vaccination of adenovirus-vectored COVID-19 vaccine (Ad5-nCoV). We also investigated the human longitudinal antibody responses following vaccination and demonstrated how the bn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 49 publications
(47 reference statements)
1
10
1
Order By: Relevance
“…6 ). Conversely to what found in SP2 3 , we did not observe the expansion of Class 3 targeting antibody germline IGHV2-5;IGHJ4-1, which so far has been observed only in previously infected vaccinees or subjects immunized with adenoviral vectors 3 , 13 , 14 . Following this, we aimed to identify expanded clonal families within the same four donors after a second and third vaccination dose.…”
Section: Resultscontrasting
confidence: 99%
See 1 more Smart Citation
“…6 ). Conversely to what found in SP2 3 , we did not observe the expansion of Class 3 targeting antibody germline IGHV2-5;IGHJ4-1, which so far has been observed only in previously infected vaccinees or subjects immunized with adenoviral vectors 3 , 13 , 14 . Following this, we aimed to identify expanded clonal families within the same four donors after a second and third vaccination dose.…”
Section: Resultscontrasting
confidence: 99%
“…Interestingly, the IGHV1-58 germline predominant in this group was previously shown to recognize a "supersite" on the S protein surface and to be expanded following beta or omicron breakthrough infection in vaccinated individuals 10,12,20 . An interesting finding of this work is that the highly cross-reactive germline IGHV2-5;IGHJ4-1, found in subjects with hybrid immunity and in people vaccinated with viral vectors 3,14 , is absent after a third mRNA vaccine, suggesting that the induction of this germline may require endogenous production of the S protein. The lack of expansion of the IGHV2-5;IGHJ4-1 germline after three mRNA vaccine doses could partially explain the above-mentioned loss of cross-reactivity by Class 3 nAbs.…”
Section: Discussionmentioning
confidence: 79%
“…It has also been shown that cross-reactive antibodies may be boosted by vaccine or infection 12,[50][51][52] . A few structures of cross-reactive antibodies which retain activities against Omicron variants have been determined 53,54 . Among these, Sheward et al reported a VH3-53 antibody with different CDRs from YB9-258 likely to withstand Omicron variants by a different molecular mechanism 54 .…”
Section: Discussionmentioning
confidence: 99%
“…These antibodies can also be identified as ordinary antibodies or nanobodies according to their types 25 , 26 . The complex structure of many antibodies with the viral S protein or RBD domain has been resolved 5 , 27 29 . The S proteins in these complexes are diverse, including wild-type (WT) and various mutant proteins.…”
Section: Introductionmentioning
confidence: 99%